Understanding Religious Pluralism in Indonesia : Social and Religious Perspectives in the Modern Era - Achmad Robita; Khairil Anwar (International Journal of Social Science and Humanity, 2025)
Indonesia, with its vast social, cultural, and religious diversity, faces significant challenges in managing religious pluralism in the modern era. This article explores the complexities of religious pluralism in Indonesia through both social and religious perspectives. The study employs a qualitative approach using library research methods, examining various literatures encompassing pluralism theory, social theory, and contemporary phenomena related to religious pluralism in Indonesia. The analysis reveals that religious pluralism in Indonesia involves not only religious diversity but also socio-political dynamics and the growing influence of globalization, which increasingly shapes interfaith relations. Key issues include interreligious tensions often triggered by political and economic factors, as well as conflicts stemming from differing interpretations of religious teachings. This article also highlights the vital role of religion in shaping Indonesia’s social and cultural identity, along with the ongoing challenges in fostering tolerance and harmony among religious communities. Thus, the study provides insights into how religious pluralism in Indonesia can be wisely managed, considering the existing social complexities and challenges, while also offering a fresh perspective on understanding the dynamics of religious pluralism in an increasingly pluralistic Indonesian context.